Pengenalan Ababil: Program Finite Element Analysis (FEA) 3-Dimensi Untuk Struktur Rangka-Batang - Sugeng Waluyo (Dinamika Rekayasa, 2011)
Ababil is an open source computer program working on the basis offinite element method (FEM) which is aimed to analyze frame structures. It is mainly designed as a solver without embedded pre-or/and post-processing units. Recently, the solver is compatible only for reading and writing in the Gmsh [1] pre- and post-processing software environment. The FEM kinematics formulation applied here is relied on the Timoshenko Beam Theory (TBT) using linear shape function. Finally, the well-known FEM software MSC.Nastranis used to ensure the capability of Ababil in the prediction of frame deformation by means of FEMsimulation